Synthesis, characterization, conductivity, and gas‐sensing performance of copolymer nanocomposites based on copper alumina and poly(aniline‐co‐pyrrole). Issue 8 (5th May 2022) - Sankar, S.; Ramesan, M. T.
Abstract: A series of copolymer nanocomposites based on poly(aniline‐ co ‐pyrrole) (PANI‐ co ‐PPy) with different contents of copper alumina (Cu‐Al2 O3 ) nanoparticles were synthesized by benign in situ chemical oxidation polymerization. The structural, thermal transition, and morphological interpretations were carried out by Fourier‐transform infrared spectroscopy (FTIR), x‐ray diffraction (XRD), differential scanning calorimetry (DSC), and high‐resolution transmission electron microscope (HR‐TEM). The electrical properties such as alternating current (AC) conductivity and dielectric measurements were performed at room temperature to verify their application in developing new electronic devices. The presence of nanoparticles in the copolymer and the synergistic interaction in the copolymer matrix was confirmed by FTIR and XRD. HR‐TEM indicates the nanosized uniform dispersion of nanofiller in the copolymer matrix. DSC revealed a reduction in the flexibility of polymer with an increase in glass transition temperature of copolymer composites. AC conductivity measurement manifested an increased hopping of charge carriers in nanocomposites when compared with pristine PANI‐ co ‐PPy. Dielectric properties were maximum for copolymer with 5 wt% Cu‐Al2 O3 . Excellent gas sensing traits were observed for copolymer nanocomposites due to the electron transfers existing between PANI‐ co ‐PPy and ammonia gas. The maximum gas‐sensing properties and electrical conductivity were observed for 5 wt% copolymer composites. The magnificent material properties make PANI‐ co ‐PPy/Cu‐Al2 O3 nanocomposites, a promising contender for developing nano‐electronic devices. Abstract : The HR‐TEM images of different contents of Cu‐Al2 O3 incorporated copolymer nanocomposites showed the presence of spherically shaped nanofillers, which are uniformly distributed in the copolymer matrix at 5 wt% loading. When the loading of nanoparticles reached to 7 wt%, unevenly distributed nanoparticles with agglomerated morphology is visible.